COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF PT. BANK SYARIAH INDONESIA AND PT. BANK MANDIRI (PERSERO) AS THE PARENT AND CONTROLLING SHAREHOLDERS OF THE COMPANY - syukron sazly; Herudini Subariyanti; Andri Rizko Yulianto; Aliffah Kusumaningrum; Joko Ariawan; Dirgahayu Erri (Dynamic Management Journal, 2023)
The desire for a new business line to increase new income is one of the goals of conventional banks opening Islamic business units (UUS) or Islamic Commercial Banks (BUS). This goal will be achieved if the transfer of knowledge (marketing knowledge, technological knowledge and experience) and commitment to increasing resources (human resources, capital, infrastructure) from the parent company to the subsidiary companies goes well. In fact, the market share of Islamic banking is still very small compared to the conventional industry, only recorded at 7.09% and there is a large discrepancy in the performance of Islamic Business Units and Islamic Commercial Banks compared to the performance of their parent companies. The author is interested in conducting this research, with the consideration that Bank Syariah Indonesia (BSI) is the largest Islamic bank and Bank Mandiri as the holding company and controlling shareholder. The author wants to know how the performance comparison of both. Supposedly if shareholder commitment is high to its subsidiaries, then total assets, equity, net income and financial performance ratios in this case CAR, NPL, NIM, ROA, BOPO and LDR are not much different. The sample data is the financial performance of BSI and Bank Mandiri as of Quarter I 2021 to Quarter IV 2022. The columnogorov-smirnov test is used to test data normality and independent sample t-test to test hypotheses, with the SPSS 25 program. As a result, there is no simultaneous significant differences between BSI and Bank Mandiri in CAR, NPL, NIM, ROA, BOPO and LDR or all financial performance indicators, but partially there are significant differences for all of these financial performance indicators